2002
DOI: 10.1002/cncr.10638
|View full text |Cite
|
Sign up to set email alerts
|

Paget disease of the nipple

Abstract: BACKGROUND The treatment of Paget disease by mastectomy has been challenged recently in favor of breast‐conserving techniques. A large series of patients treated with mastectomy has been reviewed to assess the feasibility of less radical surgery. METHODS The cases of 70 women with a clinical diagnosis of Paget disease were reviewed. The type, grade, receptor and node status, and the mammographic and pathologic extent of the underlying breast malignancy were determined. The survival of patients with invasive di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(31 citation statements)
references
References 18 publications
1
29
1
Order By: Relevance
“…Kothari et al 13. reported that patients with PD-IDC had a significantly lower survival (10-year OS 49%) than patients with IDC only (64%).…”
Section: Discussionmentioning
confidence: 99%
“…Kothari et al 13. reported that patients with PD-IDC had a significantly lower survival (10-year OS 49%) than patients with IDC only (64%).…”
Section: Discussionmentioning
confidence: 99%
“…[1112] Approximately 50% of this patients present with an associated palpable mass in the breast. [34] In cases where mass is palpable, invasive carcinoma is likely to be found.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…[13] The tumors which may or may not be palpable, located usually close to areola, tend to be central and are often multifocal. [11] Patients with periphery localized tumors also have been reported. In one study, Chaudary et al .…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammography findings include skin thickening, malignant calcification, or masses at the level of the nipple, architectural distortion, and nipple retraction. However, the literature reports that the mammography can be negative in 22%–50% of patients [2, 5, 13, 14]. As underlying carcinoma is common even in women with a benign mammogram and no palpable mass, the breast US and MRI may be useful in detecting the lesion.…”
Section: Discussionmentioning
confidence: 99%